Experimental study and discrete element simulation of sand-steel interface behaviour. - Fu, Tieming. (University of Ottawa (Canada), 1998)
The main objectives of this study are to explore the possibility of simulating sand-steel interface behaviour using the Discrete Element Method, to investigate numerically the movements of particles in sand-steel interface tests, and to simulate experimentally the liquefaction phenomenon. In the first part, sand-steel interface tests were conducted using an automated 3-D apparatus C3DSSI (Cyclic 3-Dimensional Simple Shear Testing of Interfaces). A dense sand-rough steel plate interface test was carried out under constant normal stress conditions and the results were used in the discrete element simulations. The tests on the loose sand-smooth steel plate interface samples were carried out to investigate the effects of the initial state of the sample (i.e., relative density and normal stress) and the boundary conditions on the sand-steel interface behaviour. In the second part, an attempt was made to explore the advantages and limitations of using the discrete element method to simulate the behaviour of an interface between a granular soil and a steel plate. A two-dimensional discrete element program PFC$\rm\sp{2D}$ was used in the simulations. (Abstract shortened by UMI.)
Keywords: Engineering, Civil.